2021
DOI: 10.1038/s41598-021-94418-8
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis induces endothelial dysfunction in mice

Abstract: The treatment of periodontitis has numerous positive effects on established chronic health conditions, including cardiovascular disease and diabetes. However, ethical considerations do limit the establishment of human trials to investigate whether periodontitis promotes the early stages of chronic conditions. Therefore, the aim of this study was to investigate whether periodontitis induces endothelial dysfunction in hyperlipidemic apolipoprotein E gene-deficient (ApoE-/-) mice. Forty-five 8-week-old ApoE-/- mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…Specifically, there was a decrease in functional capillary density, capillary diameters, red blood cell velocity at rest, endotheliumindependent vasodilatation, and post-ischemic peak flow in patients with periodontitis. Other experimental findings have also supported the passive impact of periodontitis on function of vascular endothelium (Brito et al, 2013;Lira-Junior et al, 2014;Parvaneh et al, 2021).…”
Section: The Effect Of Periodontal Therapy On Vascular Endothelial Fu...mentioning
confidence: 69%
See 1 more Smart Citation
“…Specifically, there was a decrease in functional capillary density, capillary diameters, red blood cell velocity at rest, endotheliumindependent vasodilatation, and post-ischemic peak flow in patients with periodontitis. Other experimental findings have also supported the passive impact of periodontitis on function of vascular endothelium (Brito et al, 2013;Lira-Junior et al, 2014;Parvaneh et al, 2021).…”
Section: The Effect Of Periodontal Therapy On Vascular Endothelial Fu...mentioning
confidence: 69%
“…The reduced bioavailability of NO can inhibit the expression of adhesion molecules and promote SMCs migration and proliferation (Liccardo et al, 2019;Yang et al, 2022;Suh et al, 2019), further aggravating aberrant function of VECs. Recently, Parvaneh et al (Parvaneh et al, 2021) established periodontitis in 8-week-old ApoE -/mice and showed that periodontitis exhibited impaired endothelial-dependent vasorelaxation responses to acetylcholine, which was indicative of NO bioactivity impairment and the onset of ED. Similarly, Campi et al (Campi et al, 2016) have found that after 7 days of the induction of periodontitis, the vascular response of adult rat aorta was impaired in terms of norepinephrine-induced contraction and acetylcholine-dependent relaxation, and the endothelium-derived NO and cyclooxygenase 2 (COX-2) were involved in the process (Zhou et al, 2019;De Oliveira et al, 2021).…”
Section: The Influence Of Periodontitis On Vascular Endothelial Functionmentioning
confidence: 99%
“…Adipose and vascular tissue of insulin-resistant patients are in a persistent condition of low-grade inflammation and are infiltrated with several classes of immune cells 111 Increased C-reactive protein levels in periodontal disease compared with controls; 112 reduced systemic inflammation following periodontal therapy 115,116 Arterial wall thickness People with type 2 diabetes have a higher carotid intima media thickness compared with nondiabetic controls with an estimated difference of 0.13 mm after adjusting for traditional risk factors 26 Increased carotid intima media thickness compared with controls 14,123 Endothelial dysfunction Flow-mediated dilation was found to be impaired in diabetic patients compared with nondiabetic individuals [125][126][127] Worse flow-mediated dilation of brachial artery in periodontal disease, 128 with improvements after treatment 117,129 Arterial stiffness Increased arterial stiffness in alterations of glucose homeostasis 34,130 Increased pulse-wave velocity compared with health or gingivitis 134,135 Cardiovascular disease Two-to fourfold excess risk of cardiovascular disease 83,136 Periodontal disease measures, including pocket depths, bleeding on probing, and number of teeth, associated with cardiovascular disease [137][138][139] Cardiovascular death 80% of all deaths of diabetic patients are attributable to cardiovascular disease [23][24][25] Increased risk of cardiovascular disease mortality [140][141][142] Note: Where possible, systematic reviews and meta-analyses are indicated as references.…”
Section: Diabetes Periodontitismentioning
confidence: 99%
“…A meta‐analysis demonstrated that periodontal disease diagnosis was associated with a mean difference in flow‐mediated dilation of 5.1% compared with controls and that a mean improvement of 6.6% between test and control was observed after periodontal treatment 123 . A recent experimental study showed that induced periodontitis in mice led to endothelial dysfunction 129 …”
Section: Introductionmentioning
confidence: 99%
“…9 In the presence of periodontitis, these episodes of bacteraemia are more frequent, of longer duration and consist of more virulent bacterial species. 9 Pathogenic oral bacteria associated with periodontitis have been identified in atherothrombotic tissues, and in animal models periodontal pathogens have been shown to induce endothelial dysfunction 10 and accelerate atherosclerosis. 5 This supports a direct effect of periodontal pathogens on atheroma formation suggesting that bacteraemia is a likely mechanism linking periodontitis and CVD.…”
Section: Bacteraemia and Inflammation: Biological Mechanisms Linking ...mentioning
confidence: 99%